HKS Misinfo Review 2022
DOI: 10.37016/mr-2020-94
|View full text |Cite
|
Sign up to set email alerts
|

A story of (non)compliance, bias, and conspiracies: How Google and Yandex represented Smart Voting during the 2021 parliamentary elections in Russia

Abstract: On 3 September 2021, the Russian court forbade Google and Yandex to display search results for “Smart Voting,” the query referring to a tactical voting project by the jailed Russian opposition leader Alexei Navalny. To examine whether the two search engines complied with the court order, we collected top search outputs for the query from Google and Yandex. Our analysis demonstrates the lack of compliance from both engines; however, while Google continued prioritizing outputs related to the opposition’s web res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…An additional cross-country audit found Google to be effective at suppressing pro-Kremlin content in five countries (Toepfl et al, 2021). Additionally, one audit compared Google and Yandex rankings of content related to Alexei Navalny and found that Google promoted opposition sources more frequently than Yandex (Makhortykh et al, 2022). Search engine audit studies are useful but are constrained by the set of keyphrases chosen by the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…An additional cross-country audit found Google to be effective at suppressing pro-Kremlin content in five countries (Toepfl et al, 2021). Additionally, one audit compared Google and Yandex rankings of content related to Alexei Navalny and found that Google promoted opposition sources more frequently than Yandex (Makhortykh et al, 2022). Search engine audit studies are useful but are constrained by the set of keyphrases chosen by the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the varying notions of authoritative sources: while both Google and Yandex may prioritize sources of the same type (e.g. journalistic outlets), the exact choice of sources varies substantially with Google prioritizing more independent media, which are often critical of the Kremlin, and Yandex often giving priority to pro-Kremlin media (Makhortykh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at the time of our research, Yandex was intensively targeted in Russia by legal regulatory mechanisms that dictated which websites to exclude from search results (e.g., news websites not registered with the Russian state communications oversight agency, Roskomnadzor ; Wijermars, 2021 ) and which information to forward to authorities ( Meduza, 2020 ). As for indirect influence, it was generally suggested that Yandex avoided conflicts with authorities by adapting to Russia’s restricted media freedom realities so as not to jeopardise its economic profits ( Daucé and Loveluck, 2021 ), whereas Google, in contrast, could afford not to comply (e.g., Makhortykh et al, 2022 ). Daucè and Loveluck (2021) , in their audit of Yandex’s news aggregator, concluded that Yandex is a ‘key asset in the Russian government’s overall disciplining of the country’s media and digital public sphere’ (p. 1).…”
Section: Context: Yandex and The History Of Its Appropriation By The ...mentioning
confidence: 99%
“…Aiming at assessing the sociopolitical consequences of search engine behaviour, a growing number of studies in the realm of political communication have recently implemented ‘algorithmic audits’ ( Mittelstadt, 2016 : 4992). For instance, researchers have analysed the diversity of search results ( Puschmann, 2019 ; Steiner et al, 2020 ; Trielli and Diakopoulos, 2019 ; Unkel and Haim, 2019 ; Urman et al, 2021a ), examined the presence of various biases in search results ( Kravets and Toepfl, 2021 ; Makhortykh et al, 2022 ) and investigated the influence of search personalisation ( Haim et al, 2018 ; Kliman–Silver et al., 2015 ). Auditing specifically the Kremlin-controlled search engine Yandex, extant research has demonstrated that the algorithms of this Russia-based intermediary are often biased toward the interests of the country’s ruling elites ( Daucè and Loveluck, 2021 ; Kravets and Toepfl, 2021 ; Makhortykh et al, 2022 ; Wijermars, 2021 ).…”
mentioning
confidence: 99%